Investigating the inhibitory mechanism of aketoglutarate analogues towards human collagen prolyl 4-hydroxylase - Peh, Keng Hee (My University, 2014)
Collagen is a structural protein essential in wound healing and the formation of connective tissues in humans. Despite its importance, overproduction of collagen can be a potential threat to human life. Production of functional collagen is facilitated by the enzyme collagen prolyl 4-hydroxylase (CP4H). CP4H catalyzes the post-translation modification of proline residues in collagen to form (2S, 4R)-4-hydroxyproline, which is essential for collagen stability. a-ketoglutarate(AKG) is one of the essential co-substrates used by CP4H for hydroxylation of proline residues. CP4H is a target for anti-fibrotic treatments, although inhibitors of CP4H have yet to be developed as therapeutics. In this experiment, we designed an electrophilic AKG analogue based upon a known CP4H inhibitor, pyridine-2,5-dicarboxylic acid, and aim to study its inhibitory potency on human CP4H.